Making Large‐Area Titanium Disulfide Films at Reduced Temperature by Balancing the Kinetics of Sulfurization and Roughening. (2nd July 2020) - Li, Yifei; Singh, Akshay; Reidy, Kate; Jo, Seong Soon; Ross, Frances M.; Jaramillo, Rafael
Abstract: The synthesis of large‐area TiS2 thin films is reported at temperatures as low as 500 °C using a scalable two‐step method of metal film deposition followed by sulfurization in an H2 S gas furnace. It is demonstrated that the lowest‐achievable sulfurization temperature depends strongly on the oxygen background during sulfurization. This dependence arises because TiO bonds present a substantial kinetic and thermodynamic barrier to TiS2 formation. Lowering the sulfurization temperature is important to make smooth films, and to enable integration of TiS2 and related transition metal dichalcogenides—including metastable phases and alloys—into device technology. Abstract : Lowering the temperature needed to make thin films of transition metal dichalcogenides (TMDs) is important for device integration. TiO bonds present a substantial kinetic and thermodynamic barrier to TiS2 formation. The temperature needed to make large‐area TiS2 films by metal sulfurization can be reduced by hundreds of Celsius by controlling the background oxygen concentration throughout the process.